THE ROLE OF THE SOCIAL ENVIRONMENT IN THE DEVELOPMENT OF COMMUNICATIVE SKILLS IN PRESCHOOL CHILDREN - Ibragimova Shahnoza Gapparovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides valuable information about the role and importance of the family and preschool education organization in developing communicative skills in children of preschool age.